Perancangan Bilah Inverse Taper Pada Turbin Angin Sumbu Horizontal Skala Kecil - Tegar Imaniar Kusnanto; Oktarina Heriyani; Dan Mugisidi; Yos Nofendri (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2023)
Renewable energy is renewable and non-polluting energy. One of the new renewable energies is wind, Indonesia itself has an average wind speed of around 3-6 m/s. Wind turbines are tools used to convert wind energy into electrical energy, small-scale wind turbines are wind turbines that have a maximum output power of no more than 500 watts. There are several components in a wind turbine such as generators, fins, controllers, data loggers, batteries and blades. One of the important components in a wind turbine is the blade because the blade is the component that is directly facing the wind. If what is designed is an inverse taper type blade which has a widening shape towards the end by applying the cross sectional shape of the NACA 6412 airfoil. The performance test of the blade is carried out for 3 days with the highest wind speed data acquisition of 8.12 m/s at 13:00 noon and electric power the highest obtained was 136.53 watts at 13:00 noon